Slovanski jug v mariborskih spomenikih in imenih ulic - Čoh Kladnik, Mateja (Studia Historica Slovenica, 2024)
Based on archival sources and the literature, the authors address the question of how the Slavic South shaped the image of Maribor after World War I. They note that at the end of the war, with the change in the system of government and the socio-political order, the city continued to develop according to the urban plan adopted at the end of the 19th century. The city's new strategic location and the change in its national and political structure and dynamics brought about radical changes which were also reflected in the naming and renaming of streets, and in the construction and demolition of monuments.
Keywords: Kingdom of Serbs, Croats and Slovenes; Kingdom of Yugoslavia; Kraljevina Jugoslavija; Kraljevina Srbov, Hrvatov in Slovencev; Maribor; monuments; Slovenian territory; slovensko ozemlje; spomeniki; streets; ulice